2014
DOI: 10.3389/fnmol.2014.00027
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of PTEN produces autism-like behavioral deficits and alterations in synaptic proteins

Abstract: Many genes have been implicated in the underlying cause of autism but each gene accounts for only a small fraction of those diagnosed with autism. There is increasing evidence that activity-dependent changes in neuronal signaling could act as a convergent mechanism for many of the changes in synaptic proteins. One candidate signaling pathway that may have a critical role in autism is the PI3K/AKT/mTOR pathway. A major regulator of this pathway is the negative repressor phosphatase and tensin homolog (PTEN). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
148
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 50 publications
(68 reference statements)
13
148
0
Order By: Relevance
“…Both increased anxiety and lack of appropriate fear are reported in human ASD, and this range of behaviors is also seen in models of neuronal Pten loss. The Gfap-Cre; Pten loxP/loxP model exhibits lower than usual anxiety levels in combination with hyperactivity, while the Nse-cre; Pten loxP/loxP mouse showed high levels of anxiety-like behavior, as well as increased locomotion in the open field test [62,87]. The Pten m3m4 model also demonstrated poor balance on the accelerating rotarod task, potentially in keeping with the motor clumsiness reported in individuals with high-functioning ASD [61,89].…”
Section: Autism-like Behavioral Phenotypes In Mouse Models Of Pten Lomentioning
confidence: 65%
See 2 more Smart Citations
“…Both increased anxiety and lack of appropriate fear are reported in human ASD, and this range of behaviors is also seen in models of neuronal Pten loss. The Gfap-Cre; Pten loxP/loxP model exhibits lower than usual anxiety levels in combination with hyperactivity, while the Nse-cre; Pten loxP/loxP mouse showed high levels of anxiety-like behavior, as well as increased locomotion in the open field test [62,87]. The Pten m3m4 model also demonstrated poor balance on the accelerating rotarod task, potentially in keeping with the motor clumsiness reported in individuals with high-functioning ASD [61,89].…”
Section: Autism-like Behavioral Phenotypes In Mouse Models Of Pten Lomentioning
confidence: 65%
“…Compared with wild-type mice, the first model to demonstrate reduced social behavior was the Nse-cre; Pten loxP/loxP mouse, which showed a reduced preference for another mouse than a nonsocial object [62]. This decrease in social behavior was replicated in later models based on Pten loss in more restricted populations, such as granule cells of the dentate gyrus and cerebellum or neural progenitors in adult animals [67,87]. Having established the critical role of neuronal Pten activity for normal social behavior, other models add context for what may occur in PHTS where PTEN mutations are germline and behavioral phenotypes are the collective expression of this pathology in every cell type.…”
Section: Autism-like Behavioral Phenotypes In Mouse Models Of Pten Lomentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have shown that mTOR signaling is linked to ASD (Tsai et al, 2012) (Lugo et al, 2014) (Garg et al, 2013). Dysregulation of upstream mTOR signaling leads to ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral tests discussed above can be readily applied to autism models as well. Mice with a deletion of PTEN (a gene involved in the regulation of the mTOR pathway) had deficits in SP, SC, and marble burying (56). Mice with BTBR mutations express autistic features (on SC test) but are not seizure-prone.…”
Section: Perspective On Animal Models Of Autismmentioning
confidence: 99%